Differential diagnosis of plasma cell dyscrasias in rheumatological practice - V I Vasilyev; V R Gorodetsky; Oksana Alekseyevna Logvinenko; N A Probatova; E Yu Varlamova; A I Pavlovskaya; M A Frenkel; S Kh Sedyshev; S G Palshina; E L Nasonov (Современная ревматология)
Plasma cell dyscrasias (PCD) present certain difficulties in differentially diagnosing with autoimmune rheumatic diseases (RD) as they have some clinical and laboratory manifestations that are characteristic of the latter. Objective: to generalize the experience in diagnosing PCD at the Research Institute of Rheumatology (RIR), Russian Academy of Medical Sciences (RAMS). Subjects and methods. Nineteen patients admitted to the RIR, RAMS, for rheumatological referral diagnoses were diagnosed as having different types of PCD, both PCD in the presence of RD (n = 10) and primary PCD without RD (n = 9). Immunochemical studies of serum and urinary proteins and bone marrow trepanobiopsy were performed in all the patients. Histological studies were made of the minor salivary glands (n = 12), lymph nodes (n = 3), parotid salivary glands - PSG (n = 5), spleen (n = 1), cranial bones (n = 2) and humerus (n = 1). The immunophenotype of tumor lymphocytes in the biopsy and trepanobiopsy specimens were determined by an immunoflurenscence method with standard monoclonal antibody panels and the paraffin sections of biopsy specimens were examined by an immunoperoxidase technique. Biopsy and trepanobiopsy speciments and myelograms were assessed by the researchers of the N.N. Blokhin Russian Cancer Research Center, RAMS. Results. Over 10 years of follow-up, 19 patients (13 females and 6 males) were diagnosed as having different types of PCD: multiple myeloma (MM) (n = 9), extramedullary plasmacytoma of lymph nodes (n = 2), solitary plasmacytoma (SP) of bone (n = 2), Bence-Jones myeloma (BJM) (n = 2), primary amyloidosis (PA) (n = '), lymphoplasmacytic lymphoma (n = '), Waldenström's macroglobulinemia (WM) (n = 2). In the presence of RA, '0 patients with PCD developed Sjogren's disease (SD) (n = 7), rheumatoid arthritis (RA) + SD (n = 2), RA (n = '); and 9 patients had primary PCD (MM (n = 5), BJM (n = '), WM (n = '), SP (n = '), and PA (n = ')). These 9 patients with different rheumatological diagnoses were long followed up and referred to the RIR, RAMS, to specify these. One third of the patients had recurrent conjunctivitis, enlarged PSG and xerostomia (55%). Arthralgias, arthritis of minor and large joints, flexion contractures of hands, ossalgias, and pains in the lumbar spine and ribs were present in '0-45% of the patients. Vascular lesions, such as Reynaud's phenomenon, recurrent purpuras, lower extremity ulcerative lesions, and toe gangrenes, were observed in '0-35% of the patients with PCD. Lesions in the reticuloendothelial system, such as lymphadenopathy, splenomegaly ('5%), hepatomegaly (45%), and fever (25%), were also detected. Conclusion. Many clinical and laboratory manifestations of primary PCD and RD are similar and only the absence of classical laboratory markers of autoimmune disease, as well as the presence of serum monoclonal immunoglobulins and urinary Bence Jones protein suggest the presence of PCD, both primary PCDs and those with RD.